Implementation of Disclosure of Human Capital Reporting in Creating Corpo-rate Value at PT. Semen Indonesia - Ratna Achjuningrum Achjuningrum; Dwi Suhartini (Future Science, 2021)
This study aims to analyze and describe how the disclosure of human capital reporting based on the principles of Human Resources Management (HRM), Human Resources Accounting (HRA) and Human Capital Management (HCM) in the annual report of PT. Semen Indonesia can create corporate value. Human capital is the most important capital for the company. Skills, knowledge and behavior that are well managed are expected to give the best contribution to support efforts to achieve the company's vision and mission. This research is a qualitative research using content analysis method. This study concludes that the disclosure of human capital reporting that is in line with the principles of HRM, HRA and HCM can create company value even though it only implements the disclosure pattern without the use of costs, metrics and indicators of achievement.